Penguatan Pendidikan Karakter Peserta Didik Usia Dini Melalui Kerjasama Pendidik Dan Wali Murid Dalam Meningkatkan Kemampuan Sosial Emosional Peserta Didik Pada Program Pembiasaan Diri - Hanifa Hafiza; M. Fauzi; Misbahul Huda (Alzam: Journal of Islamic Early Childhood Education, 2023)
This early age is a period of students in developing their potential, it is hoped that at this age there is a need for educational stimulation. From the stimulation obtained by early childhood students, it will improve all aspects of its development, one of the aspects developed by early childhood students is the social emotional aspect. The purpose of writing a conceptual article is to add insight into the collaboration of educators and students' parents in improving emotional social skills in the student's self- habituation program. The form of collaboration between educators and guardians of students in developing socio-emotional students through several activities including WhatsApp groups, classes and character books. The goal to be achieved in this form of collaboration is to improve social emotional abilities, such as: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. The self-accustoming programs implemented include (1) habituation, (2) spontaneous habituation, (3) exemplary habituation, (4) conditioning